2017
DOI: 10.1007/s13205-016-0585-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on prevalence of microbial contamination on the surface of raw salad vegetables

Abstract: The present work evaluates the microbiological quality of raw salad vegetables (RSV) consumed in Dhanbad city, India. A total of 480 samples of 8 different raw salad vegetables from local market were examined for overall microbial quality in terms of aerobic mesophilic, psychrotrophic counts, yeast, mould and total coliform levels. E. coli O157:H7, Listeria monocytogenes and Salmonella sp. were detected by real-time polymerase chain reaction (qPCR) subsequent to isolation. Results showed that all the samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 30 publications
7
51
3
Order By: Relevance
“…A higher count was reported earlier by Kubheka et al [29] in South Africa, as the 55 salads collected from street vendors had an ACC mean value of 5.9 (±0.6) log CFU/g and the count ranged between 2.7 and 8.9 log CFU/g. Another higher ACC mean value was reported in a study done in India by Mritunjay and Kumar [30] , where a total of 480 samples of eight different raw salad vegetables from local markets had a mean AMC of 6.1 log CFU/g, ranging from 2.0 to 9.6 log CFU/g.…”
Section: Discussionmentioning
confidence: 67%
“…A higher count was reported earlier by Kubheka et al [29] in South Africa, as the 55 salads collected from street vendors had an ACC mean value of 5.9 (±0.6) log CFU/g and the count ranged between 2.7 and 8.9 log CFU/g. Another higher ACC mean value was reported in a study done in India by Mritunjay and Kumar [30] , where a total of 480 samples of eight different raw salad vegetables from local markets had a mean AMC of 6.1 log CFU/g, ranging from 2.0 to 9.6 log CFU/g.…”
Section: Discussionmentioning
confidence: 67%
“…; Korir et al . ; Mritunjay and Kumar ). However, a study conducted in India reported high prevalence (39·2%) of E. coli in fresh produce (Viswanathan and Kaur ).…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the low prevalence (5·1%) of Salmonella in vegetables/fruits is corroborated with other studies, where this pathogen was detected at 4·0% (Singh et al . ; Mritunjay and Kumar ). One of the studies conducted in India on raw produce, reported much higher (28·1%) prevalence of this pathogen (Viswanathan and Kaur ).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Sabbithi et al (2014) reported that 58.5% of the carrots used in the salads sold as street food in Hyderabad, India, were contaminated with Salmonella. In Dhanbad, India, 3.3% of the carrots collected from the local market were contaminated with Salmonella (Mritunjay and Kumar, 2017).…”
Section: Full Papermentioning
confidence: 99%
“…Apart from Salmonella, other microbial pathogens such as E. coli, L. monocytogenes, S. aureus, may grow in cabbages (Mritunjay and Kumar, 2017). According to the studies done by Prazak et al (2002) and Kuan et al (2017), 4.7% and 18.2% of cabbages were contaminated by L. monocytogenes in Texas, United States and Selangor, Malaysia respectively.…”
Section: Full Papermentioning
confidence: 99%